Glutathione-responsive and -exhausting metal nanomedicines for robust synergistic cancer therapy - Liu, Peng; Hao, Lu; Liu, Min; Hu, Shuo (Frontiers in Bioengineering and Biotechnology, 2023)
Owing to rapid and uncontrolled proliferation, the cancer cells are characterized by overexpression of glutathione (GSH), which impairs reactive oxygen species (ROS)-based therapy, as well as weakens the chemotherapeutic agents-induced toxification. Over the past few years, extensive efforts have been devoted to improving therapeutic outcomes by depleting intracellular GSH. Especially, varieties of metal nanomedicines with the capacity of GSH responsiveness and exhaustion have been explored and applied for anticancer applications. In this review, on basis of high concentration of intracellular GSH in cancer cells, we introduce several GSH-responsive and -exhausting metal nanomedicines that can specifically ablate tumor, including inorganic nanomaterials, metal-organic frameworks (MOFs) and platinum-based nanomaterials. Afterwards, those metal nanomedicines extensively applied in synergistic cancer therapy are discussed in detail, including chemotherapy, photodynamic therapy (PDT), sonodynamic therapy (SDT), chemodynamic therapy (CDT), ferroptotic therapy and radiotherapy. Finally, the horizons and challenges in the field are also presented for future development.